2020
DOI: 10.3233/jad-190706
|View full text |Cite
|
Sign up to set email alerts
|

Improving Choroid Plexus Segmentation in the Healthy and Diseased Brain: Relevance for Tau-PET Imaging in Dementia

Abstract: Recent studies have revealed the possible role of choroid plexus (ChP) in Alzheimer's disease (AD). T1-weighted MRI is the modality of choice for the segmentation of ChP in humans. Manual segmentation is considered the gold-standard technique, but given its time-consuming nature, large-scale neuroimaging studies of ChP would be impossible. In this study, we introduce a lightweight segmentation algorithm based on the Gaussian Mixture Model (GMM). We compared its performance against manual segmentation as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(68 citation statements)
references
References 30 publications
(32 reference statements)
7
46
0
Order By: Relevance
“…Consistently with previous studies, we showed that it is inaccurate for this specific brain structure. 12,13 As expected, FastSurfer required much less computational time than FreeSurfer. It was also slightly more accurate.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Consistently with previous studies, we showed that it is inaccurate for this specific brain structure. 12,13 As expected, FastSurfer required much less computational time than FreeSurfer. It was also slightly more accurate.…”
Section: Discussionsupporting
confidence: 66%
“…11 Nevertheless, its segmentation of CP is highly inaccurate. 12,13 Hence, the development of more accurate automatic CP segmentation methods would be very useful to allow the study of large cohorts. To the best of our knowledge, only two other approaches have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…These findings were replicated in a first-episode schizophrenia (FES) study by Zhou et al, where they found greater CP volume in FES, which was correlated with higher allostatic load (indexed by subclinical cardiovascular, metabolic, neuroendocrine, and immune markers) [ 96 ]. The results from these two neuroimaging studies are promising, which taken together with the expanding interest of the CP in psychiatry and neurology [ 86 , 96 , 97 ], adds to the importance of ensuring accurate segmentation of the CP with more reliable and accurate tools [ 81 ].…”
Section: The Neuropathological Role Of the Choroid Plexus In Neuropsy...mentioning
confidence: 99%
“…Positron emission tomography (PET) imaging is also being used to study the human CP. Thus, total AV1451 (tau) PET binding to the CP using Gaussian Mixed Model segmentation can distinguish between patients with AD from those with mild cognitive impairment [52].…”
Section: Choroid Plexusmentioning
confidence: 99%